Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/ndt/gfw017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rituximab dose on infectious complications in ABO-incompatible kidney transplantation

Abstract: Standard RIT increased the risk of serious infection when compared with reduced-dose RIT. Reduced-dose RIT might be sufficient for ABOi KT without increasing the risk of serious infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 39 publications
3
36
1
Order By: Relevance
“…[12] In our results, rituximab dose did not show significant association with PCP occurrence; this result may be due to the abrupt and long-lasting effects of B-cell depression, and because the incidence of PCP was too small to obtain statistical significance. [12] CD4 + T lymphocytes orchestrate the defense against P. jiroveci, and low CD4+ T lymphocyte count is thus suggested as an independent risk factor associated with PCP in solid organ transplant recipients. [2] In vivo studies have suggested a mechanism for how rituximab may increase the risk of PCP by inducing B-cell depletion: [23,24] Lind et al showed that owing to the absence of P. jiroveci-specific antibody, mice with B-cell deficiency are more vulnerable to PCP, showing that as antigen presenting cells, B-cells play an important role in the defense response against P. jiroveci.…”
Section: Risk Factors Associated With Pcpcontrasting
confidence: 65%
See 3 more Smart Citations
“…[12] In our results, rituximab dose did not show significant association with PCP occurrence; this result may be due to the abrupt and long-lasting effects of B-cell depression, and because the incidence of PCP was too small to obtain statistical significance. [12] CD4 + T lymphocytes orchestrate the defense against P. jiroveci, and low CD4+ T lymphocyte count is thus suggested as an independent risk factor associated with PCP in solid organ transplant recipients. [2] In vivo studies have suggested a mechanism for how rituximab may increase the risk of PCP by inducing B-cell depletion: [23,24] Lind et al showed that owing to the absence of P. jiroveci-specific antibody, mice with B-cell deficiency are more vulnerable to PCP, showing that as antigen presenting cells, B-cells play an important role in the defense response against P. jiroveci.…”
Section: Risk Factors Associated With Pcpcontrasting
confidence: 65%
“…In our retrospective study using the database of a single large center, we showed that perioperative rituximab treatment had 3.09 times higher hazards of PCP occurrence after adjusting for other risk factors, which is in line with the results of previous studies. [2,5,7,8] Rituximab dose was suggested to be related with serious infectious complications following transplant, [11,12] with Lee et al reporting that recipients treated with standard dose rituximab had higher risk of fungal infection than those who received lower dose of rituximab. [12] In our results, rituximab dose did not show significant association with PCP occurrence; this result may be due to the abrupt and long-lasting effects of B-cell depression, and because the incidence of PCP was too small to obtain statistical significance.…”
Section: Risk Factors Associated With Pcpmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of serious infection was reported to be more frequent with standard rituximab (375 mg/m 2 ) than with reduced-dose rituximab (200 mg/m 2 ). 22 In addition, Gulleroglu and associates 23 reported that the combined use of rituximab with additional treatments such as antithymocyte globulin, IVIg, and repeated plasma exchange may be associated with high risk of infections. They recommended closely monitoring these patients, especially those who receive T-cell-depleting agents.…”
Section: Discussionmentioning
confidence: 99%